Preparation method and application of natural polyphenol coated superparamagnetic nanoparticles
The preparation of natural polyphenol-encapsulated superparamagnetic iron oxide nanoparticles through continuous flow synthesis method, solving the problem of low bioavailability of gallic acid in the inflammatory site, realizing the dual functions of anti-inflammatory treatment and MRI contrast, and improving the stability of the drug in the body sex and bioavailability.
Patent Information
- Application Number
- CN202411263966.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
As an anti-inflammatory drug, gallic acid has problems with low bioavailability and rapid clearance, which limits its application in disease treatment, especially in the inflammatory site, which is difficult to achieve effective concentrations.
The natural polyphenol-encapsulated superparamagnetic iron oxide nanoparticles were prepared by continuous flow synthesis method. The iron source precursor solution containing Fe2+ and Fe3+ was reacted with alkali to form superparamagnetic iron oxide, and reacted with gallic acid to form nanoparticles. Use the ELVIS effect to achieve selective accumulation in the inflammatory site and improve the bioavailability of drugs.
It realizes stable packaging and selective accumulation of natural polyphenols, improves the bioavailability of anti-inflammatory drugs and MRI contrast function. As an MRI contrast agent and anti-inflammatory therapeutic agent, it has dual functions, extends the time the drug is in the body, and enhances the Treatment and diagnosis effects.
Smart Images

Figure CN119113130A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical diagnosis and treatment, and specifically relates to a preparation method and application of natural polyphenol-coated superparamagnetic nanoparticles. Background Art
[0002] Inflammation is a natural defense response to stimuli such as infection, injury, and toxins. However, a large number of studies have shown that excessive inflammatory responses can lead to many diseases, including autoimmune diseases, degenerative diseases, cancer, etc. It is well known that inflammatory responses are closely related to the excessive production of reactive oxygen species (ROS). The continued excessive presence of ROS not only induces oxidative damage, cell apoptosis, and necrosis, but also aggravates the degree of inflammation. Therefore, restoring the balance of ROS is the key to treating inflammation.
[0003] Gallic acid (GA) is a natural polyphenolic compound that can be obtained in large quantities through natural resources or biochemical methods. Scientific studies have shown that GA has a significant ability to scavenge reactive oxygen species (ROS), which makes it play an important role in the anti-inflammatory and antioxidant defense system. However, like many other small molecule compounds, GA faces the problems of low bioavailability and rapid clearance, which makes it difficult to reach the required effective concentration at the lesion site. This limitation has, to a certain extent, restricted the application of GA in disease treatment. To overcome these obstacles, researchers are exploring different strategies, such as nanotechnology, to improve the stability and bioavailability of GA, thereby enhancing its potential in clinical treatment.
[0004] In recent years, the rapid development of nanotechnology has confirmed that nano-drug delivery platforms are an effective means to improve the delivery efficiency of small molecule anti-inflammatory drugs. Similar to the enhanced permeability and retention (EPR) effect at the tumor site, nano-delivery systems of a certain size have also been shown to selectively accumulate at the site of inflammation through vascular extravasation and subsequent inflammatory cell-mediated sequestration (ELVIS) effect. As delivery carriers for inflammatory treatment, nanoparticles have many advantages over traditional formulation methods: 1) increase the stability of drugs in circulation; 2) prevent drugs from being biologically cleared and prolong half-life; 3) use the ELVIS effect to achieve selective accumulation at the site of inflammation. In addition, a variety of nanoparticles with potential therapeutic properties have been developed, such as PAMAM dendrimers and metal nanomaterials. Despite this, a large number of studies have focused on evaluating the therapeutic potential of gallic acid in inflammatory models. Given that early diagnosis and timely treatment of inflammation are crucial to improving cure rates and reducing mortality, exploring the application of gallic acid in diagnostic reagents may be more practical than simply using it as a therapeutic means.
[0005] Superparamagnetic iron oxide nanoparticles (SPIO) are an interesting class of nanomaterials that have been extensively studied as magnetic resonance contrast agents due to their high biocompatibility, excellent magnetic properties, and ease of surface functionalization. SPIO nanoparticles have a long blood circulation time and are used for drug delivery, which can not only improve the delivery efficiency but also prolong the time of the drug in the body, achieving a long-lasting effect. Therefore, it is crucial to achieve a controllable synthesis of SPIO nanoparticles of varying size. Recently, a continuous flow synthesis strategy has been demonstrated to enable the scalable and controllable preparation of SPIO nanoparticles. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and (biological) application of natural polyphenol-coated superparamagnetic nanoparticles (i.e., superparamagnetic iron oxide nanoparticles), wherein the natural polyphenol is gallic acid, and the superparamagnetic iron oxide nanoparticles are used as magnetic resonance contrast agents and anti-inflammatory therapeutic agents.
[0007] To achieve the purpose of the present invention, the following embodiments are provided.
[0008] In one embodiment, the use of a natural polyphenol-coated superparamagnetic nanoparticle of the present invention as an MRI contrast agent and an anti-inflammatory agent, wherein the natural polyphenol is gallic acid, and the natural polyphenol-coated superparamagnetic nanoparticle is prepared by the following method, which comprises: 2+ and Fe 3+ The iron source precursor solution is reacted with alkali, the generated superparamagnetic iron oxide reacts with natural polyphenol gallic acid, and the reaction product solution is dialyzed to obtain the product.
[0009] Furthermore, in the above-mentioned use of the present invention, in which the method for preparing superparamagnetic nanoparticles coated with natural polyphenols has a reaction temperature of 30-70°C, preferably 60°C.
[0010] Further, the use of the present invention, the Fe-containing 2+ and Fe 3+ The iron source precursor solution is reacted with a base, and the reaction time is 2-10s, preferably 5-7s, and more preferably 7s.
[0011] Preferably, in the above-mentioned use of the present invention, in which the method for preparing superparamagnetic nanoparticles coated with natural polyphenols, the reaction is carried out using a continuous flow reactor.
[0012] In another embodiment, the present invention provides a method for preparing natural polyphenol-coated superparamagnetic nanoparticles using continuous flow, wherein the natural polyphenol is gallic acid, and the method comprises the following steps:
[0013] 1) Alkali and Fe 2+ and Fe 3+The iron source precursor solution is preheated and pumped into the first mixer for mixing, and then enters the reactor 1 for reaction;
[0014] 2) mixing the reaction product of step 1) with the pumped gallic acid solution in the second mixer, and then entering the reactor 2 for reaction;
[0015] 3) placing the product solution flowing out of the reactor 2 in a dialysis bag for dialysis, collecting the solution in the dialysis bag, filtering the membrane, and concentrating by ultrafiltration to obtain superparamagnetic iron oxide nanoparticles coated with natural polyphenols.
[0016] In some preferred embodiments, in the method of the present invention, in step 1), the alkali and the iron precursor solution are pumped in at a flow rate of 3-7 ml / min, more preferably 5 ml / min, the alkali is sodium hydroxide solution, the iron precursor solution, Fe 2+ with Fe 3+ The molar ratio of Fe 2+ Derived from FeSO4, the Fe 3+ Derived from FeCl3, the preheating temperature and the reaction temperature are 30-70°C, more preferably 60°C, and the reaction time in reactor 1 is 2s-10s, more preferably 5s-7s.
[0017] In some preferred embodiments, in the above method of the present invention, in step 2), the flow rate of pumping gallic acid solution is 1.5-3.5 ml / min, more preferably 2.5 ml / min; the reaction temperature is 30-70°C, more preferably 60°C; the reaction time in reactor 2 is 0.5-2 min, preferably 0.5 min.
[0018] In some preferred embodiments, in the above method of the present invention, in step 3), the filter membrane size is 220 nm.
[0019] In the above-mentioned uses and methods of the present invention, the natural polyphenol has a structure shown in Formula I,
[0020]
[0021] The natural polyphenol-coated superparamagnetic iron oxide nanoparticles ("superparamagnetic nanoparticles" for short) of the present invention have the strong antioxidant properties of natural polyphenol gallic acid and the MRI angiography function of iron oxide. As nanomaterials, they can utilize the ELVIS effect to achieve selective accumulation at the site of inflammation, thereby improving the bioavailability of anti-inflammatory drugs.
[0022] The superparamagnetic iron oxide nanoparticles wrapped by natural polyphenols of the present invention have good transverse relaxation performance and longitudinal relaxation performance (r1: 8.92mM -1 s -1 ; r2: 23.0mM-1 s -1 ), can be used as an excellent magnetic resonance T1-T2 dual-mode contrast agent. In addition, the natural polyphenol-encapsulated superparamagnetic iron oxide nanoparticles of the present invention can be used as both MRI contrast diagnostic agents and anti-inflammatory therapeutic agents. Compared with traditional iron oxide nanoparticles, they have therapeutic functions; compared with small molecule natural polyphenol materials, they not only improve the utilization rate of drugs, but also have imaging diagnostic functions, can achieve visualization of diseases while exerting therapeutic effects, and have MRI contrast and anti-inflammatory integrated functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic structural diagram of superparamagnetic iron oxide nanoparticles coated with natural polyphenol gallic acid of the present invention;
[0024] Figure 2 It is a schematic diagram of the continuous flow reaction equipment and the process of synthesizing nanoparticles;
[0025] Figure 3 The transmission electron microscopy image (A) and the transmission electron microscopy statistical graph of superparamagnetic iron oxide nanoparticles coated with natural polyphenols, and the dynamic light scattering particle size distribution graph of superparamagnetic iron oxide nanoparticles coated with natural polyphenols in Examples 1-3;
[0026] Figure 4 It is a fitting diagram of T1 and T2 relaxation efficiency of superparamagnetic iron oxide nanoparticles coated with natural polyphenols in Examples 1, 2 and 3 at 0.5T;
[0027] Figure 5 The T1 and T2 weighted imaging effects of different concentrations of aqueous solutions of superparamagnetic iron oxide nanoparticles coated with natural polyphenols in Examples 1, 2, and 3 at 3.0T;
[0028] Figure 6 is the zeta potential of the superparamagnetic iron oxide nanoparticles coated with natural polyphenols in Example 3;
[0029] Figure 7 The XRD pattern of the superparamagnetic iron oxide nanoparticles coated with natural polyphenols in Example 3;
[0030] Figure 8 This is the total antioxidant capacity curve of the superparamagnetic iron oxide nanoparticles coated with natural polyphenols in Example 3. DETAILED DESCRIPTION
[0031] The following examples are merely representative and are used to further understand the spirit of the present invention, but are not intended to limit the scope of the present invention.
[0032] The schematic diagram of the structure of the natural polyphenol-coated superparamagnetic iron oxide nanoparticles of the present invention is shown in Figure 1 .
[0033] Natural polyphenol-coated superparamagnetic iron oxide nanoparticles can be prepared in batches using continuous flow. The continuous flow reaction equipment and the process flow diagram of the synthesized nanoparticles are shown in the figure. Figure 2 As shown, the particle size of iron oxide nanoparticles can be controlled by adjusting the iron oxide generation time (2s-7s).
[0034] Example 1 Gallic acid coated superparamagnetic iron oxide nanoparticles
[0035] The preparation method specifically comprises the following steps:
[0036] A 0.57 M sodium hydroxide solution and a 0.1 M mixed solution of ferrous sulfate heptahydrate and ferric chloride hexahydrate (Fe 2+ :Fe 3+ The method comprises the following steps: the first step is to prepare a novel nanostructured carbon foam and a nanostructured carbon foam, wherein the nanostructured carbon foam is prepared by mixing a 0.18M natural polyphenol gallic acid solution pumped in at a flow rate of 2.5 ml / min at a molar ratio of 1:2 at a flow rate of 5 ml / min, preheated at 60°C and mixed in a first mixer, and then mixed and then introduced into a reactor 1 to react for 2 seconds; the reaction product solution is mixed in a second mixer with a 0.18M natural polyphenol gallic acid solution pumped in at a flow rate of 2.5 ml / min, and then mixed and then introduced into a reactor 2 to react for 30 seconds; after the reaction is completed, the outflowing product solution is placed in a dialysis bag for dialysis, and the solution in the dialysis bag is collected, filtered through a 220 nm filter membrane, and concentrated by ultrafiltration to obtain uniform and stable natural polyphenol gallic acid-coated superparamagnetic iron oxide nanoparticles (i.e., gallic acid-coated superparamagnetic nanoparticles).
[0037] Example 2 Gallic acid coated superparamagnetic iron oxide nanoparticles
[0038] The preparation method specifically comprises the following steps:
[0039] A 0.57 M sodium hydroxide solution and a 0.1 M mixed solution of ferrous sulfate heptahydrate and ferric chloride hexahydrate (Fe 2+ :Fe 3+ The method comprises the following steps: the first step is to prepare a novel nanostructured carbon foam and a nanostructured carbon foam, wherein the nanostructured carbon foam is mixed with a 0.18M natural polyphenol gallic acid solution pumped in at a flow rate of 2.5 ml / min at a molar ratio of 1:2 at a flow rate of 5 ml / min, preheated at 60°C and mixed in a first mixer, and then mixed and then introduced into a reactor 1 for reaction for 5 seconds; the reaction product solution is mixed with a 0.18M natural polyphenol gallic acid solution pumped in at a flow rate of 2.5 ml / min in a second mixer, and then introduced into a reactor 2 for reaction for 30 seconds; after the reaction is completed, the outflowing product solution is placed in a dialysis bag for dialysis, and the solution in the dialysis bag is collected, filtered through a 220 nm filter membrane, and concentrated by ultrafiltration to obtain uniform and stable natural polyphenol gallic acid-coated superparamagnetic iron oxide nanoparticles (i.e., gallic acid-coated superparamagnetic nanoparticles).
[0040] Example 3 Gallic acid coated superparamagnetic iron oxide nanoparticles
[0041] The preparation method specifically comprises the following steps:
[0042] A 0.57 M sodium hydroxide solution and a 0.1 M mixed solution of ferrous sulfate heptahydrate and ferric chloride hexahydrate (Fe 2+ :Fe 3+ The method comprises the following steps: the first step is to prepare a novel nanostructured carbon foam and a nanostructured carbon foam, wherein the nanostructured carbon foam is mixed with a 0.18M natural polyphenol gallic acid solution pumped in at a flow rate of 2.5 ml / min at a molar ratio of 1:2 at a flow rate of 5 ml / min, preheated at 60°C and mixed in a first mixer, and then mixed and reacted in a reactor 1 for 7 seconds; the reaction product is mixed with a 0.18M natural polyphenol gallic acid solution pumped in at a flow rate of 2.5 ml / min in a second mixer, and then mixed and reacted in a reactor 2 for 30 seconds; after the reaction is completed, the outflowing product solution is placed in a dialysis bag for dialysis, and the solution in the dialysis bag is collected, filtered through a 220 nm filter membrane, and concentrated by ultrafiltration to obtain uniform and stable natural polyphenol gallic acid-coated superparamagnetic iron oxide nanoparticles (i.e., gallic acid-coated superparamagnetic nanoparticles).
[0043] Example 4 Structural characterization and property determination of gallic acid-coated superparamagnetic iron oxide nanoparticles prepared
[0044] 1. Particle size and distribution test
[0045] The superparamagnetic nanoparticles coated with gallic acid obtained in Example 3 were tested using a transmission electron microscope. The test results are as follows: Figure 3 A shows the transmission electron microscopy statistics. Figure 3 As shown in B.
[0046] The particle size and particle size distribution of the natural polyphenol gallic acid-coated superparamagnetic iron oxide nanoparticles (i.e., gallic acid-coated superparamagnetic nanoparticles) prepared in Examples 1-3 were measured by dynamic light scattering. The results are as follows: Figure 3 As shown in Figure C, the dynamic light scattering particle size distribution results of the nanoparticles show that the average particle sizes of the nanoparticles obtained in the reactor 1 of Examples 1-3 are 6.65, 8.32, and 12.0 nm, respectively, when the reaction time is 2s, 5s, and 7s. The test results prove that the size of the nanoparticles can be well controlled by adjusting the reaction time of the reactor 1.
[0047] 2. Contrast effect characteristic test
[0048] The iron concentration in the nanoparticle solution was determined by atomic absorption. The gallic acid-coated superparamagnetic iron oxide nanoparticles prepared in Examples 1-3 were prepared into solution samples with different iron concentrations of 0.1, 0.2, 0.3, 0.4, and 0.5 mM, respectively, and the T1 and T2 relaxation times of each sample were measured by a 0.5T magnetic resonance relaxation efficiency instrument, and the T1 and T2 relaxation efficiencies (r1 and r2) were calculated. The results are shown in FIG. Figure 4As shown, the results show that the relaxation efficiencies of the nanoparticles prepared by the reaction time of 2s, 5s, and 7s in reactor 1 at 0.5T are: r1 = 2.43, 5.63, and 8.92 mM, respectively. -1 s -1 , r2=5.82、15.8、23.0mM - 1 s -1 , r2 / r1=2.40, 2.81, 2.58.
[0049] 3.0T in vitro imaging test, in vitro imaging effect is as follows Figure 5 As shown, the results show that the gallic acid-coated superparamagnetic nanoparticles prepared in Examples 1-3 have good T1 and T2 enhancement effects under the 3.0T magnetic resonance used in clinical practice (increasing MRI signals in T1-weighted imaging and reducing MRI signals in T2-weighted imaging). Due to the application of the material as a magnetic resonance contrast agent, under the conditions of suitable particle size, the preparation conditions with the maximum relaxation efficiency and the best effect are preferred, that is, the superparamagnetic nanoparticles coated with gallic acid prepared by the product of 7s in reactor 1 have the maximum relaxation efficiency and the best effect, which are used for subsequent experiments.
[0050] 3. Zeta potential test
[0051] The zeta potential of gallic acid (GA) and the superparamagnetic iron oxide nanoparticles (SPIO@GA) coated with gallic acid prepared in Example 3 was detected. The obvious change in potential before and after coating proved that the superparamagnetic iron oxide nanoparticles coated with gallic acid were successfully prepared. The results are shown in Figure 6 shown.
[0052] 4. Crystal form test
[0053] The superparamagnetic iron oxide nanoparticles coated with gallic acid prepared in Example 3 were subjected to X-ray diffraction detection. The peak positions in the spectrum were consistent with those of known Fe3O4 crystals, proving that the prepared nanoparticles were magnetite. Figure 7 .
[0054] 5. Antioxidant activity test
[0055] Gallic acid was prepared into gallic acid solutions of different concentrations, and the gallic acid-coated superparamagnetic iron oxide nanoparticles prepared in Example 3 were prepared into solutions of different concentrations. The total antioxidant capacity of gallic acid and gallic acid-coated superparamagnetic iron oxide nanoparticle solutions was determined using an ABTS detection kit. The results are as follows: Figure 8 As shown, the results indicate that gallic acid-coated superparamagnetic iron oxide nanoparticles have anti-inflammatory and antioxidant potential.
[0056] The above test results show that the gallic acid-coated superparamagnetic nanoparticles of the present invention can be used for magnetic resonance T1-T2 dual-function contrast agents. Compared with the T1 contrast agents (gadolinium agents) currently used in clinical practice: ① There is no risk of producing nephrogenic systemic fibrosis and residual gadolinium in the body; ② The material used is iron oxide nanoparticles, which are iron-based materials and are endogenous metal elements required by the human body, and have high biological safety; ③ As a nano contrast agent, it not only has a higher T1 relaxation efficiency, but also has a longer blood half-life and imaging time window; ④ It is a T1-T2 dual-function nano contrast agent, which can provide more complete multi-mode cross-confirmation information in magnetic resonance imaging. In addition, the natural polyphenol-coated superparamagnetic iron oxide nanoparticles of the present invention can be used as diagnostic and therapeutic agents at the same time. Compared with small molecule natural polyphenol materials, it not only improves the utilization rate of drugs, but also has the function of image diagnosis, which can realize the visualization of diseases while exerting therapeutic effects.
[0057] The above embodiments are only typical, and any simple modifications and adaptations made within the spirit and essence of the present invention fall within the protection scope of the present invention.
Claims
1. A method for using natural polyphenol-coated superparamagnetic nanoparticles as an MRI contrast agent and an anti-inflammatory agent, wherein the natural polyphenol is gallic acid, and the natural polyphenol-coated superparamagnetic nanoparticles are prepared by the following method, which comprises: 2+ and Fe 3+ The iron source precursor solution is reacted with alkali, the generated superparamagnetic iron oxide reacts with natural polyphenol gallic acid, and the reaction product solution is dialyzed to obtain the product.
2. The use according to claim 1, wherein the reaction temperature is 60°C.
3. The use as claimed in claim 1, wherein the Fe 2+ and Fe 3+ The iron source precursor solution is reacted with a base, and the reaction time is 2-10s, preferably 5-7s.
4. The use according to claim 1, wherein the method and the reaction are carried out in a continuous flow reactor.
5. A method for preparing superparamagnetic nanoparticles coated with natural polyphenols by continuous flow, wherein the natural polyphenols are gallic acid. The following steps are involved: 1) Alkali and Fe 2+ and Fe 3+ The iron source precursor solution is preheated and pumped into the first mixer for mixing, and then enters the reactor 1 for reaction; 2) mixing the reaction product of step 1) with the pumped gallic acid solution in the second mixer, and then entering the reactor 2 for reaction; 3) placing the product solution flowing out of the reactor 2 in a dialysis bag for dialysis, collecting the solution in the dialysis bag, filtering the membrane, and concentrating by ultrafiltration to obtain superparamagnetic iron oxide nanoparticles coated with natural polyphenols.
6. The method according to claim 5, wherein in step 1), the alkali and the iron precursor solution are pumped in at a flow rate of 3-7 ml / min, preferably 5 ml / min, the alkali is sodium hydroxide solution, the iron precursor solution, Fe 2+ with Fe 3+ The molar ratio is 1:
2.
7. The method according to claim 5, wherein in step 1), the preheating temperature and the reaction temperature are 30-70°C, preferably 60°C, and the reaction time in the reactor 1 is 2s-10s, preferably 5s-7s.
8. The method according to claim 5, wherein in step 2), the flow rate of the gallic acid solution pumped in is 1.5-3.5 ml / min, preferably 2.5 ml / min; the reaction temperature is 30-70° C., preferably 60° C.; and the reaction time in reactor 2 is 0.5-2 min, preferably 0.5 min.
9. The method according to claim 5, wherein in step 3), the filter membrane size is 220 nm.
10. The method of claim 5 or 6, wherein the Fe 2+ From FeSO 4 , the Fe 3+ From FeCl 3 .
Citation Information
Patent Citations
Method for preparing N,N-dimethyl-(R)-1-[(S)-2-(diphenylphosphine)ferrocenyl]ethylamine by microreactor
CN108456235A
Tannin(TA)-ferrum-BSA nanometer particle T1-MRI contrast agent and preparation method thereof
CN109847073A
Magnetic ferroferric oxide nanoparticles as well as preparation method and application thereof
CN114306650A
Preparation method of magnetic resonance imaging nano probe for pH visualization
CN114558150A
Curcumin coated magnetite nanoparticles for biomedical applications
US20140369938A1
